From plough to policy - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Environment and Development Agency TrustFrom plough to policy Some organisations seem to evolve in line with time, some of them even running a little bit ahead of the wind. The South African organisation EDA is one such. Now known as the...